Smart Investment for Redundancies Selection Integrated to Reconfigurable Fault-Tolerant Control Design - Luppi, Patricio Alfredo (2016)
This paper presents a methodology for the optimal hardware redundancies selection in the context of reconfigurable fault-tolerant control design. Assuming that a nominal controller of reduced dimension has been successfully designed, the objective is to accommodate a presumed set of failures, including partial, total, and simultaneous actuator faults, preserving the system stability and maintaining an acceptable dynamic performance. The methodology is based on a multiobjective optimization framework to obtain a suitable trade-off between conflicting design objectives such as controllability and performance. The selection of additional hardware devices (not included in the nominal controller) is penalized to determine the minimum number of redundancies that should be installed. In addition, the redundancies selection is performed without explicitly considering the type of control structure. The effectiveness of the proposed approach is tested using the well-known Tennessee Eastman benchmark.